PENINGKATAN KEMAMPUAN MELAKUKAN RESUSITASI JANTUNG PARU MENGGUNAKAN MEDIA POLKESBAN KOMPRESI SIMULATOR PADA SISWA SMA DI KOTA TANGERANG - Wasliyah, Siti; Wijonarko, Bangun (Jurnal Medikes (Media Informasi Kesehatan), 2020)
Out-Hospital Cardiac Arrest (OHCA) is a cardiac arrest event that occurs outside the hospital. Patients who experience OHCA rely on the community to provide support as the closest person when the attack occurs. The simulation training method is considered as one of the most effective and most frequently used methods for teaching CPR actions. In the implementation of the simulation needed appropriate media in the form of phantom that has been designed in such a way as to resemble the human condition. Phantom media is considered more expensive and less efficient when used as outdoor media, so this study provides an alternative substitute media in the RJP training simulation in the form of Polkesban Compression simulator. This research is a quasi-experimental study with a pretest and postets group design approach, aimed at identifying the effect of the Polkesban Compression Simulator on the Ability to Perform RJP in High School Students in the city of Tangerang. The study was conducted in June - November 2019 with a population of high school students in Tangerang City. The sampling method used was consecutive sampling totaling 50 people. The results showed there was an increase in ability in each intervention and control group, and there were significant differences in the measurements before and after the intervention (P value 0,000). In the statistical test of the two groups, the p value was 0.016 (P value ≤ 0.005), so it can be concluded that there were significant mean differences between the phantom group and PKS group, where the average PKS group was higher than the Phantom group.